Challenges in Predicting Financial Distress in Emerging Economies: The Case of Croatia. Issue 1 (2nd January 2018) - Tomas Žiković, Ivana
Abstract : Using an extensive dataset of over 44, 000 firms for a period that includes an economic upswing and a recession, this article examines how time-varying, firm-specific variables and changes in the macroeconomic environment affect the probability of firms' financial distress. Traditional single-period approaches used to predict financial distress are based on unrealistically restrictive assumptions and cannot dynamically account for changes in financial indicators and macroeconomic conditions. Therefore discrete-time hazard models (using logit and cloglog) are applied; these indicate that the probability of distress is strongly influenced by both ﬁrm-speciﬁc and macroeconomic variables. Although firm-specific variables play an essential role, the results show that macroeconomic variables are important for understanding the fluctuations in the probability of distress over time. Furthermore, the findings provide evidence that both the legal criteria and a firm's financial health should be considered when identifying firms in emerging economies that are in distress because existing bankruptcy laws are not applied.